Heat stress during grain filling affects activities of enzymes involved in grain protein and starch synthesis in waxy maize - Huan Yang (Nature Portfolio, 2018)
Abstract High temperature (temperature over 35 °C) is an extremely important environmental factor that affects the maize grain quality in Southern China. The effects of heat stress after pollination on grain protein and starch deposition and activities of involved enzymes were studied in a pot trail in 2014 and 2015. Results showed that grain dry weight reductions at maturity were 19.8% and 19.1%, whereas starch contents (mg g−1) were reduced by 3.0% and 3.3%, and starch accumulation (mg grain−1) were reduced 22.2% and 21.8% in 2014 and 2015, respectively. Protein content was decreased by heat stress before 15 DAP and increased thereafter. At maturity, protein contents (mg g−1) were increased by 24.5% and 25.3% in 2014 and 2015, while protein accumulation (mg grain−1) were not affected by heat stress. In response to heat stress, glutamate synthase activity was enhanced by 29.1–82.9% in 2014 and 2.0–141.8% in 2015, whereas glutamine synthetase activity was reduced by 1.9–43.5% in 2014 and 0.1–27.4% in 2015 throughout the grain filling. The activities of sucrose phosphate synthase were decreased by heat stress at 10–25DAP (12.7–32.0%) in 2014 and 15–20 DAP (23.2–27.5%) in 2015, and activities of sucrose synthase were decreased by heat stress at 5–15 DAP (20.0–45.0%) in 2014 and 15 DAP (22.0%) in 2015, repectively. The activities of enyzmes that involved in starch synthessis were all suppressed by heat stress during grain filling, and the reduction of adenosine diphosphate-glucose pyrophosphorylase, soluble starch synthase, and starch branching enzyme were decreased by 21.3–43.1%, 19.1–29.2%, and 7.0–45.6% in 2014 and 1.8–78.5%, 21.4–51.2%, and 11.0–48.0% in 2015, respectively. Conclusively, grain weight and starch deposition were suppressed by heat stress due to the decreased activities of enzymes involved in starch synthesis, and the increased protein content was due to the enhanced activity of glutamate synthase.